2016
DOI: 10.1016/j.tcmj.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative herpetic endophthalmitis—A case report

Abstract: We report a case of herpetic endophthalmitis following cataract surgery. A 65-year-old man underwent uneventful phacoemulsification and vision improved within the first few postoperative days. However, visual loss with an anterior chamber reaction of ++++ and a ++ vitreous cell were noted in the 4th postoperative week. Repeated intravitreal injection of vancomycin and ceftriaxone, pars plana vitrectomy and removal of the intraocular lens (IOL), and the capsular bag were performed sequentially but in vain. Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…They also found one case of postoperative endophthalmitis in their retrospective series. Yang et al reported a case of herpetic endophthalmitis in a 65-year-old man after uneventful phacoemulsification [ 28 ]. However, their case was presented in the fourth week after the surgery and was diagnosed as HSV endophthalmitis after serological testing of the capsular bag.…”
Section: Discussionmentioning
confidence: 99%
“…They also found one case of postoperative endophthalmitis in their retrospective series. Yang et al reported a case of herpetic endophthalmitis in a 65-year-old man after uneventful phacoemulsification [ 28 ]. However, their case was presented in the fourth week after the surgery and was diagnosed as HSV endophthalmitis after serological testing of the capsular bag.…”
Section: Discussionmentioning
confidence: 99%